DESKRIPSI SEBARAN JENIS DAN SIFAT FISIKA BAMBU DI KAWASAN HUTAN DENGAN TUJUAN KHUSUS (KHDTK) SENARU - Febriana Tri Wulandari (Lambung Mangkurat University-Indonesia, 2022)
Senaru specific destination forested area is the only educational forested area which is situated in Lombok Island. It has important roles in providing facilities and information supporting knowledge of bamboo characteristics growing naturally in this area. Many studies about the characteristics of bamboo have been done, but none has been conducted for this area. The information about bamboo distribution was important to understand the potency of bamboo of this area and the information about bamboo physical characteristics were used as raw material data for bamboo crafting, furniture, and simple constructions. The aims of this study were at understanding the bamboo distributions and the physical characteristics of bamboo of this area. Samplings were conducted in two phases which the first phase was collecting bamboo species, number of the bamboo clumps and sticks. The second phase was conducted several tests for the physical characteristics of the bamboo collected from the first stage. The results of this testing were described and compared to the existing bamboo quality standards. 6 (six) bamboo species were identified in this forest: yellow bamboo (Bambusa vulgaris var. striata), Petung bamboo (Dendrocalamus asper (Schult. f.) Backer ex Heyne), ampel bamboo (Bambusa vulgaris Schrad. ex J.C), Santong bamboo (Gigantochloa atter (Hassk.) Kurz), Bilis bamboo (Schizostachyum lima (Blanco) Merr) and Tali bamboo (Gigantolochloa apus Kurz). The number of bamboo clump was 160 clumps and 299 individuals. The physical characteristics of the bamboo were: fresh moisture content ranged between 37,93% – 69,49%, air-dried moisture content between 8,84% - 12,10%, fresh density ranged between 0,32 – 1,03, air-dried density ranged between 0,59 – 1,11 and oven-dried density between 0,55 – 1,04.